FLUCTUATIONS IN THE DYNAMICS OF OPPORTUNITIES AND CHALLENGES FOR MICRO, SMALL AND MEDIUM ENTERPRISES IN INDONESIA - Manalu, Hotmarilitua; Sudarmiatin, Sudarmiatin; Wardana, Ludi Wishnu (PUSAT KEWIRAUSAHAAN UNIVERSITAS BALIKPAPAN, 2024)
Are the dynamics and resilience of business actors in the Micro, Small, and Medium Enterprises (MSMEs) sector experiencing obstacles caused by government policies? This study attempts to answer the above questions. The use of bibliometric analysis with a qualitative approach is the main framework of this study. The data used is secondary data based on the collection of literature in the form of journals, books, and official websites. The dynamics related to Micro, Small, and Medium Enterprises are indeed very fluctuating and experience many obstacles in the field caused by many factors. These obstacles come from internal markets such as development, technology and external markets such as government pressure - top-down policies. The solution that can be an alternative for business actors is to carry out transformation by following the development of the times. Then, following the flow of government policy is an alternative for business actors so that they can minimize conflicts that occur throughout the dynamics and resilience of Micro, Small, and Medium Enterprises